DEVELOPMENT OF CANVAS MODEL BUSINESS-BASED COOPERATIVES: IDEAS IN THE DEVELOPMENT OF INDEPENDENT HOUSES OF WORSHIP IN MEDAN CITY - Barus, Elida Elfi; Nasution, Venny Fraya Hartini; Ichsan, Reza Nurul; Syahbudi, Muhammad; Barus, Irwan Irawadi (Universitas Pembinaan Masyarakat Indonesia, 2025)
Research background: The Medan City Government has programmed to establish a house-of-worship-based cooperative, namely a mosque with the